Marriage Certificate and Protection of Children’s Rights Due to the Unregistered Marriage in the Cianjur District in the Post Regional Regulation Number 10 in 2010 - Kamarusdiana Kamarusdiana; Triana Aprianita (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
The regional regulation number 10 in 2010 talks about the implementation of an integrated population administration. This instruction is a type of a Cianjur District government’s legal breakthrough in terms of the manifestation of an access into justice by marriage certificate (isbat nikah). This rule is due to the phenomenon of unregistered marriage certificate (nikah siri) caused by diverse factors. Here, three organizations collaborate in establishing this marriage certificate. They are Religious Courts, Ministry of Religious Affairs, and Department of Population and Civil Registration. This certificate marriage helps fulfil the basic rights of children and those of family of unregistered-marriage-certificate couples. For example, they have some important documents, such as marriage book, family card, birth certificate, and children’s identity card.